A social norms approach to changing school children's perceptions of tobacco usage. Issue 6 (2nd October 2017) - Sheikh, Afzal; Vadera, Sunil; Ravey, Michael; Lovatt, Gary; Kelly, Grace
Abstract : Purpose: Over 200, 000 young people in the UK embark on a smoking career annually, thus continued effort is required to understand the types of interventions that are most effective in changing perceptions about smoking amongst teenagers. Several authors have proposed the use of social norms programmes, where correcting misconceptions of what is considered normal behaviour lead to improved behaviours. There are a limited number of studies showing the effectiveness of such programmes for changing teenagers' perception of smoking habits, and hence this paper reports on the results from one of the largest social norms programmes that used a variety of interventions aimed at improving teenagers' perceptions of smoking. The paper aims to discuss this issue. Design/methodology/approach: A range of interventions were adopted for 57 programmes in year nine students, ranging from passive interventions such as posters and banners to active interventions such as student apps and enterprise days. Each programme consisted of a baseline survey followed by interventions and a repeat survey to calculate the change in perception. A clustering algorithm was also used to reveal the impact of combinations of interventions. Findings: The study reveals three main findings: the use of social norms is an effective means of changing perceptions, the level of interventions and change in perceptions are positively correlated, and that the most effective combinations of interventions include the use of interactive feedback assemblies, enterprise days, parent and student apps and newsletters to parents. Originality/value: The paper presents results from one of the largest social norm programmes aimed at improving young people's perceptions and the first to use clustering methods to reveal the impact of combinations of intervention.